Polymeric Nanosuspensions for Enhanced Dissolution of Water Insoluble Drugs. (22nd October 2013) - Yadollahi, Roya; Vasilev, Krasimir; Prestidge, Clive A.; Simovic, Spomenka
Abstract : The aim of the present research is to formulate and evaluate polymeric nanosuspensions containing three model water insoluble drugs, nifedipine (NIF), carbamazepine (CBZ), and ibuprofen (IBU) with various physicochemical properties. The nanosuspensions were prepared from hydroxypropyl methylcellulose (HPMC) and polyvinylpyrrolidone (PVP) by a cosolvent technique with polyethylene glycol (PEG-300) and water as the cosolvents. Physicochemical and morphological characteristics of the nanosuspensions (particle size, polydispersity index, and crystallinity) have been correlated with the drug release behaviour. The effects of polymer, drug ratio on the physical, morphological, and dissolution characteristics of the drugs are reported. Drug release is significantly enhanced from the nanosuspensions; for example, the maximum NIF, IBU, and CBZ concentrations after 8-hour dissolution are increased approximately 37, 2, and 1.2 times, respectively, in comparison with the pure powdered drugs. Based on this solubilization enhancement performance, the nanosuspensions have potential for increasing the orally dosed bioavailability of NIF, IBU, and CBZ.